Bioremediation of TPH in Petroleum HydrocarbonContaminated Clay Soil with an Emerging Nutrient (Solpawa SBR-X TM) - Achinike Okogbule Wonodi; R.N. Okparanma; M.J. Ayotamuno (International Journal of Pollution: Prevention & Control, 2023)
This research focuses on the bioremediation of total petroleum hydrocarbons (TPH) in petroleum hydrocarbon contaminated clay soil with an emerging nutrient (Solpawa SBR-XTM). A laboratory experiment was set up and successfully carried out in order to monitor TPH concentration among the various reactors (T1, T2, T3, and T4). This process was monitored for 7 days, 12 days, 22 days, 32 days, 42 days, and 52 days, respectively, for reactors 1, 2, 3, and 4. The results showed similar remediation trend at day 52 with little variance in reactor T2 compared to others treated apart from the control reactor, which is labelled T1. Also, close examination was carried out to ascertain the TPH reduction percentage among the various reactors. The result revealed that after 52 days of treatment, the TPH concentration reduced by 93.63%, 91.72%, and 86.05% for T2, T3, and T4 respectively, for all the treatments excluding the control (T1). This was because of the Solpawa soil conditioner (SSC) and the booster. A better reduction in TPH was observed in reactor T2 with 1265.3 mg/kg (reduction of 93.63%), which dropped below the aforesaid regulatory intervention value but was still above the target value of 50 mg/kg spelt out by the Nigeria regulatory framework. The TPH of the contaminated soil dropped from an initial average of 19086.7 mg/kg for all treatment to 1265.3 mg/kg (representing 93.63% TPH reduction) at the depth of 0.3 m after 40 days of treatment with the SSC working solution of 1:4. Overall, TPH reduction across the reactors reduced with decrease in the level of SSC in the working solution. However, there were significant differences (P > 0.005).
Keywords: Solpawa nutrient; bioremediation; clay soil; crude oil